VD_FINDINFO Arrêt / 2012 / 667 vom 18. September 2012 - VD Tribunal cantonal (2012)
INTERDICTION, TUTELLE, MALADIE MENTALE, DROIT D'ÊTRE ENTENDU, EXPERTISE PSYCHIATRIQUE | 369 al. 1 CC, 374 CC, 393 CPC